Effectiveness of Intensive Cardiac Rehabilitation in High-Risk Patients with Cardiovascular Disease in Real-World Practice - Iwona Świątkiewicz (MDPI AG, 2021)
Structured lifestyle interventions through cardiac rehabilitation (CR) are critical to improving the outcome of patients with cardiovascular disease (CVD) and cardiometabolic risk factors. CR programs’ variability in real-world practice may impact CR effects. This study evaluates intensive CR (ICR) and standard CR (SCR) programs for improving cardiometabolic, psychosocial, and clinical outcomes in high-risk CVD patients undergoing guideline-based therapies. Both programs provided lifestyle counseling and the same supervised exercise component. ICR additionally included a specialized plant-based diet, stress management, and social support. Changes in body weight (BW), low-density lipoprotein cholesterol (LDL-C), and exercise capacity (EC) were primary outcomes. A total of 314 patients (101 ICR and 213 SCR, aged 66 ± 13 years, 75% overweight/obese, 90% coronary artery disease, 29% heart failure, 54% non-optimal LDL-C, 43% depressive symptoms) were included. Adherence to ICR was 96% vs. 68% for SCR. Only ICR resulted in a decrease in BW (3.4%), LDL-C (11.3%), other atherogenic lipids, glycated hemoglobin, and systolic blood pressure. Both ICR and SCR increased EC (52.2% and 48.7%, respectively) and improved adiposity indices, diastolic blood pressure, cholesterol intake, depression, and quality of life, but more for ICR. Within 12.6 ± 4.8 months post-CR, major adverse cardiac events were less likely in the ICR than SCR group (11% vs. 17%), especially heart failure hospitalizations (2% vs. 8%). A comprehensive ICR enhanced by a plant-based diet and psychosocial management is feasible and effective for improving the outcomes in high-risk CVD patients in real-world practice.